Second hand smoke attributable disease burden in 204 countries and territories, 1990–2021: a systematic analysis from the Global Burden of Disease Study 2021 - Zheng Su; Ying Xie; Zhenxiao Huang; Anqi Cheng; Xinmei Zhou; Min Wang; Xin Xia; Tingfen Ji; Liang Zhao; Zhao Liu; Dan Xiao; Chen Wang (Respiratory Research)
Abstract Background We aimed to estimate the changes in, second hand smoke (SHS) and potential drivers of its health outcome from 1990 to 2021 worldwide. Methods The data was derived from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021, which covered 204 countries and territories. We reported SHS changes by sex, year and sociodemographic index (SDI) level (a summary measure that identifies where countries or other geographic areas sit on the spectrum of development) from 1990 to 2021. We analyzed the risk-outcome pairs among all age groups to estimate disease burden attributable to SHS exposure and also did a decomposition method to attribute changes in all-cause SHS attributable deaths or disability-adjusted life years (DALYs) to population growth, population aging, and mortality change. Results Worldwide, the age-standardized summary exposure values (SEV) of SHS exposure in 2021 was 30.6% (28.9 to 31.6) for males and 38.0% (35.5 to 39.0) for females, with a percentage change of −0.2 (−0.2 to −0.1) and −0.3 (−0.3 to −0.2), respectively, since 1990. Among the top 10 countries with the highest SEV, there were mainly high-middle SDI countries for male and low-middle SDI and middle SDI countries for female, respectively. Secondly, about 1.29 million deaths (0.68–1.90) and 34.90 million DALYs (17.95–52.21) were attributable to SHS exposure, and about half of them took place in two countries (China and India). Ischemic heart disease (IHD) (29.67%), chronic obstructive pulmonary disease (COPD) (19.04%), and lower respiratory infections (LRIs) (10.87%) were the three leading causes of SHS associated deaths. Lastly, since 2010, the number of SHS related death significantly increased due to population growth and population aging, despite a decrease in mortality attributable to SHS exposure. Conclusion Globally, the age-standardized SEV of SHS exposure decreased from 1990 to 2021. Since 2010, the increased number of deaths attributable to SHS exposure was mainly attributable to population growth and aging.